Examining the Relationship between Systemic Immune–Inflammation Index and Disease Severity in Juvenile Idiopathic Arthritis - Delia-Maria Nicoară; Andrei-Ioan Munteanu; Alexandra-Cristina Scutca; Giorgiana-Flavia Brad; Iulius Jugănaru; Meda-Ada Bugi; Raluca Asproniu; Otilia Mărginean (Cells, 2024)
Juvenile Idiopathic Arthritis (JIA), the leading childhood rheumatic condition, has a chronic course in which persistent disease activity leads to long-term consequences. In the era of biologic therapy and tailored treatment, precise disease activity assessment and aggressive intervention for high disease activity are crucial for improved outcomes. As inflammation is a fundamental aspect of JIA, evaluating it reflects disease severity. Recently, there has been growing interest in investigating cellular immune inflammation indices such as the neutrophil-to-lymphocyte ratio (NLR) and systemic immune inflammation index (SII) as measures of disease severity. The aim of this retrospective study was to explore the potential of the SII in reflecting both inflammation and disease severity in children with JIA. The study comprised 74 JIA patients and 50 healthy controls. The results reveal a notable increase in median SII values corresponding to disease severity, exhibiting strong correlations with traditional inflammatory markers, including CRP and ESR (ρ = 0.714, ρ = 0.661), as well as the JADAS10 score (ρ = 0.690). Multiple regression analysis revealed the SII to be independently associated with JADAS10. Furthermore, the SII accurately distinguished patients with high disease activity from other severity groups (AUC = 0.827, sensitivity 81.5%, specificity 66%). These findings suggest that integrating the SII as an additional measure holds potential for assessing disease activity in JIA.